Analisis Model Komunikasi Lasswell pada Kebijakan Kartu Identitas Anak di Karawang - Azmi Ayu Fadhilah Burhanudin; Evi Priyanti; Hanny Purnamasari (VISA: Journal of Vision and Ideas, 2024)
This study aims to determine the role of government communication in disseminating information on the Child Identity Card (KIA) policy in Karawang. The research method uses descriptive qualitative research through observation, interviews and literature studies. The theory used in analyzing using the theory of Lasswell (1998) which has 5 theories namely Communicator, Communicant, Message, Media, and Effect. The results showed that the communication carried out was sufficient to fulfill Lasswell's theory of government communication, namely 1) Communicators, namely the actors involved in this policy are the Population and Civil Registration Office of Karawang Regency, 2) Communicants who receive this policy are school children such as PAUD, TK, SD, SMP, SMA who are less than 17 years old, 3) The message to be conveyed in this policy is that the Child Identity Card (KIA) is an official identity provided by the state, 4) The media used in disseminating information on this policy is through social media (Instagram, TikTok) and through minggon meetings, 5) The effect caused is that administrative data collection becomes more structured because there is personal data and identity that has been registered before.